A method for changing the decomposition pathway of pollutants by peroxymonosulfate (PMS) using the distribution pattern of copper, and a method for preparing and applying the composite catalyst
Cu-MXene composite catalysts with controlled copper distributions enhance PMS activity, addressing low activity issues in existing catalysts by optimizing metal distribution, achieving efficient pollutant decomposition and stability.
Patent Information
- Application Number
- JP2023566583
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-11-17
- Filing Date
- 2023-02-22
- Publication Date
- 2025-01-09
- Estimated Expiration
- 2043-02-22
AI Technical Summary
Existing heterogeneous catalysts for peroxymonosulfate (PMS) exhibit low activity and inefficient utilization of metal atoms, leading to limited catalytic performance in decomposing antibiotic pollutants, and the influence of metal distribution patterns on PMS activity has not been adequately addressed.
The method involves preparing Cu-MXene composite catalysts with different copper distribution patterns, including single atom, cluster, and copper film distributions, achieved through alternating pulse irradiation of precursors on a Ti 3C 2-MXene carrier, to enhance the generation and concentration of active species like 1O 2 and SO 4 ·-.
The Cu-MXene composite catalysts significantly improve the decomposition efficiency of antibiotic pollutants, achieving over 95% removal in 60 minutes with high stability and varying active species concentrations based on copper distribution patterns.
Smart Images

Figure 2025500095000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to the technical field of multifunctional water treatment and purification materials, in particular to a method for changing the decomposition pathway of pollutants by peroxymonosulfate (PMS) using the distribution pattern of copper, and the preparation method and application of the composite catalyst. [Background technology]
[0002] Due to the widespread use of antibiotics, they are frequently detected in pharmaceutical wastewater, influent and effluent from wastewater treatment plants, as well as natural waters. Sulfanilamides are a new class of organic persistent pollutants that contain an amino group, a phenyl group, a sulfonamide bridge, and an R-substituent. The sulfanilamide residue not only has potential toxicity to bacteria, algae, and plants, but also contributes to the occurrence and spread of antibiotic resistance genes and bacteria. Among the mass trace pollutant removal technologies, the peroxymonosulfate (PMS) oxidation method has attracted great attention due to its advantages of being green, efficient, environmentally friendly, and free of secondary pollution.
[0003] The development of peroxymonosulfate (PMS) catalysts with high activity and specificity is of particular importance. Currently, heterogeneous catalysts, such as metal oxides and metal-supported carbon materials (e.g., activated carbon, carbon nanotubes, biochar, and graphene oxide), are being actively researched. However, heterogeneous catalytic reactions usually occur on the catalyst surface, where the utilization of atoms is low. Hundreds of metal atoms inevitably accumulate on the catalyst, and only a small proportion of metals exhibit catalytic activity. In addition, the use of too much metal or metal oxide will result in the metal being washed out. Therefore, there is an urgent need to develop more efficient and stable catalysts that enable the rapid release and effective utilization of active species. The distribution pattern of metals (single atoms, clusters, nanoparticles) can affect the active sites of the catalyst, which can affect the generation of active species and the oxidation selectivity during pollutant decomposition. However, little attention has been paid to the effect of metal distribution patterns on peroxymonosulfate (PMS) activity, which impedes the practical application of metal catalysts to water treatment. Summary of the Invention [Problem to be solved by the invention]
[0004] The objective of the present invention is to provide a method for changing the pathway of pollutant degradation by peroxymonosulfate (PMS) using the distribution pattern of copper, and a method for the preparation and application of the composite catalyst, in order to solve the technical problem of the low activity of existing metal catalysts in the catalytic degradation of antibiotic pollutants.
[0005] In order to achieve the above objectives of the present invention, the present invention provides the following technical solutions: [Means for solving the problem]
[0006] This invention uses the distribution pattern of copper to change the decomposition pathway of pollutants by peroxymonosulfate (PMS). When the distribution pattern of copper is a single atom distribution, the active substance generated is1 O2 and SO4 ·- When the distribution pattern of copper is cluster distribution, the active substance produced is 1 O2 and SO4 ·- When the copper distribution pattern is copper film distribution, the active material produced is 1 It is characterized by being O2.
[0007] Next, if the distribution pattern of copper is a single atom distribution, 1 The steady-state concentration of O2 is 0.39×10 -9 ~0.42×10 -9 M -1 ·s -1 , SO4 ·- The steady-state concentration of is 0.02×10 -9 ~0.04×10 -9 M -1 ·s -1 If the distribution pattern of copper is clustered, 1 The steady-state concentration of O2 is 1.5×10 -9 ~1.6×10 -9 M -1 ·s -1 , SO4 ·- The steady-state concentration of is 0.21×10 -9 ~0.23×10 -9 M -1 ·s -1 If the copper distribution pattern is copper film distribution, 1 The steady-state concentration of O2 is 0.10×10 -9 ~0.12×10 -9 M -1 ·s -1 It is.
[0008] The present invention provides a method for preparing Cu-MXene composite catalysts with different copper distribution patterns, and the steps are as follows:
[0009] Using Ti3C2-MXene as the deposition support and nitrogen as the carrier gas, the deposition support is alternately pulse-irradiated with bis(dimethylamino-2-propoxy)copper(II), min.98%Cu(dmap)2 precursor and diethylzinc precursor to obtain Cu-MXene composite catalysts with different copper distribution patterns in different deposition cycles.
[0010] Next, the flow rate of the nitrogen is 40 to 60 sccm.
[0011] Next, the alternating pulses are performed at 110 to 140°C.
[0012] Next, the Bis(dimethylamino-2-propoxy)copper(II), min.98%Cu(dmap)2 precursor is preheated at a temperature of 90-110 °C, and the diethylzinc precursor is preheated at a temperature of 20-30 °C.
[0013] Furthermore, the bis(dimethylamino-2-propoxy)copper(II), min. 98% Cu(dmap)2 precursor is pulsed 50 to 200 times, and the diethylzinc precursor is pulsed 50 to 200 times.
[0014] Finally, the deposition cycles ranged from 1 to 150, with each deposition cycle consisting of a 2-second pulse of Bis(dimethylamino-2-propoxy)copper(II), min.98%Cu(dmap)2 precursor, a 5-second reaction, and a 20-second wash of Bis(dimethylamino-2-propoxy)copper(II), min.98%Cu(dmap)2, followed by a 0.5-second pulse of diethylzinc precursor, a 5-second reaction, and a 20-second wash of diethylzinc precursor.
[0015] The present invention provides Cu-MXene composite catalysts with different copper distribution patterns, including a Cu-MXene composite catalyst with a single atom distribution pattern, a Cu-MXene composite catalyst with a cluster distribution pattern, and a Cu-MXene composite catalyst with a metal film distribution pattern.
[0016] In this invention, Cu-MXene composite catalysts with different copper distribution patterns are applied to decompose antibiotic pollutants in water by activating peroxymonosulfate (PMS). Effect of the Invention
[0017] In the present invention, Cu-MXene composite catalysts with various copper distribution patterns (single atom, copper cluster, copper thin film) can be obtained.
[0018] The Cu-MXene composite catalysts prepared in the present invention are advantageous for the activation of peroxymonosulfate (PMS), and are effective in activating active oxide species (e.g., 1 O2, · OH sum SO4 ·- ), and the metal distribution pattern can induce variations in active oxide species and concentrations.
[0019] (3) The Cu-MXene composite catalyst prepared by the present invention can activate peroxymonosulfate (PMS), and the removal rate of antibiotic pollutants reaches more than 95% in 60 minutes. Continuous catalytic decomposition experiments show that the composite catalyst of the present invention has high stability. [Brief description of the drawings]
[0020] [Figure 1] 1 is a spherical aberration electron microscope photograph of the composite catalysts obtained in Examples 1 and 2 of the present invention. [Diagram 2] Cu K-edge XANES spectra using CuO, Cu2O, and Cu foil as references. [Diagram 3] FIG. 1 shows Fourier transform extended X-ray absorption fine structure (FT-EXAFS) spectrograms of Cu foil, CuO, CuO, and k3 weights of the composite catalyst of Example 2. [Figure 4] 1 shows the EXAFS fitting curve of the composite catalyst of Example 2. [Diagram 5] The degradation rate profiles of sulfanilamide in PMS systems activated by composite catalysts with different copper distribution patterns are shown. [Figure 6] 1 is a graph showing the utilization of PMS by composite catalysts with different copper distribution patterns. [Figure 7] 4 is a graph showing the cycle decomposition rate of sulfanilamide by activated PMS using the composite catalyst obtained in Example 2. [Figure 8] 1 is a graph showing the effect of the copper distribution pattern on the MXene surface on the type and steady-state concentration of reactive species generated. [Figure 9] 1 is a graph showing a comparison of the steady-state concentrations of active species in composite catalysts with different copper distribution patterns. [Figure 10] 1 is a graph showing the pathway of PMS decomposition by catalytic activation of sulfanilamide with different copper distribution patterns. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] This invention uses the distribution pattern of copper to change the decomposition pathway of pollutants by peroxymonosulfate (PMS). When the distribution pattern of copper is a single atom distribution, the active substance generated is 1 O2 and SO4 ·- When the distribution pattern of copper is cluster distribution, the active substance produced is 1 O2 and SO4 ·- When the copper distribution pattern is copper film distribution, the active material produced is 1 It is characterized by being O2.
[0022] In the present invention, when the distribution pattern of copper is a single atom distribution, 1 The steady-state concentration of O2 is 0.39×10 -9 ~0.42×10 -9 M -1 ·s -1 , SO4 ·- The steady-state concentration of is 0.02×10 -9 ~0.04×10 -9 M -1 ·s -1 If the distribution pattern of copper is clustered, 1 The steady-state concentration of O2 is 1.5×10 -9 ~1.6×10 -9 M -1 ·s -1 , SO4 ·- The steady-state concentration of is 0.21×10 -9 ~0.23×10 -9 M -1 ·s -1 If the copper distribution pattern is copper film distribution, 1 The steady-state concentration of O2 is 0.10×10 -9 ~0.12×10 -9 M -1 ·s -1 It is.
[0023] In the present invention, in order of priority, when the distribution pattern of copper is a single atom distribution, 1 The steady-state concentration of O2 is 0.40 x 10 -9 M -1 ·s-1 , SO4 ·- The steady-state concentration of is 0.03×10 -9 M -1 ·s -1 If the distribution pattern of copper is clustered, 1 The steady-state concentration of O2 is 1.55×10 -9 M -1 ·s -1 , SO4 ·- The steady-state concentration of is 0.22 × 10 -9 M -1 ·s -1 If the copper distribution pattern is copper film distribution, 1 The steady-state concentration of O2 is 0.11×10 -9 M -1 ·s -1 It is.
[0024] The present invention provides a method for preparing Cu-MXene composite catalysts with different copper distribution patterns, and the steps are as follows:
[0025] Using Ti3C2-MXene as the deposition support and nitrogen as the carrier gas, the deposition support is alternately pulse-irradiated with bis(dimethylamino-2-propoxy)copper(II), min.98%Cu(dmap)2 precursor and diethylzinc precursor to obtain Cu-MXene composite catalysts with different copper distribution patterns in different deposition cycles.
[0026] In the present invention, the flow rate of the nitrogen is 40 to 60 sccm, with 50 sccm being preferred.
[0027] In the present invention, the alternating pulses are performed at 110 to 140°C, with 115 to 130°C being preferred, and 120°C being more preferred.
[0028] In the present invention, the Bis(dimethylamino-2-propoxy)copper(II), min.98%Cu(dmap)2 precursor is preheated at a temperature of 90-110°C, with 100°C being preferred, and the diethylzinc precursor is preheated at a temperature of 20-30°C, with 25°C being preferred.
[0029] In the present invention, the Bis(dimethylamino-2-propoxy)copper(II), min. 98% Cu(dmap)2 precursor is pulsed 50-200 times, preferably 60-180 times, more preferably 70-150 times, and the diethylzinc precursor is pulsed 50-200 times, preferably 60-180 times, more preferably 70-150 times.
[0030] In the present invention, the deposition cycle is 1 to 150 times, preferably 50 to 100 times, and more preferably 80 times; in the present invention, one deposition cycle is composed of a 2-second pulse of Bis(dimethylamino-2-propoxy)copper(II), 98% or more Cu(dmap)2 (Bis(dimethylamino-2-propoxy)copper(II), min.98%Cu(dmap)2) precursor, a 5-second reaction, and a 20-second wash of Bis(dimethylamino-2-propoxy)copper(II), 98% or more Cu(dmap)2 (Bis(dimethylamino-2-propoxy)copper(II), min.98%Cu(dmap)2) precursor, followed by a 0.5-second pulse of diethylzinc precursor, a 5-second reaction, and a 20-second wash of diethylzinc precursor.
[0031] The present invention provides Cu-MXene composite catalysts with different copper distribution patterns, which include a Cu-MXene composite catalyst with a single atom distribution pattern, a Cu-MXene composite catalyst with a cluster distribution pattern, and a Cu-MXene composite catalyst with a metal film distribution pattern, with the Cu-MXene composite catalyst with the cluster distribution pattern being preferred.
[0032] In this invention, Cu-MXene composite catalysts with different copper distribution patterns are applied to decompose antibiotic pollutants in water by activating peroxymonosulfate (PMS).
[0033] In this invention, catalytic peroxymonosulfate (PMS) activation for degrading antibiotic pollutants in water is operated as follows: 0.01-0.15 g of Cu-MXene composite catalyst with different copper distribution patterns is mixed with 100-300 mL of sulfanilamide-containing Borax buffer, then 0.05-1.5 mM peroxymonosulfate (PMS) is added to complete.
[0034] In the present invention, as a priority order, it is sufficient to mix 0.012-0.14g of Cu-MXene composite catalysts having different copper distribution patterns with 150-250mL of sulfanilamide-containing borax buffer, and then add 0.1-1.2mM of peroxymonosulfate, PMS; more preferably, it is sufficient to mix 0.013g of Cu-MXene composite catalysts having different copper distribution patterns with 200mL of sulfanilamide-containing borax buffer, and then add 0.5-1.0mM of peroxymonosulfate, PMS to complete the process.
[0035] In the present invention, the concentration of sulfanilamide in the sulfanilamide-containing borax buffer is 5 to 15 mg / L, preferably 8 to 12 mg / L, and more preferably 10 mg / L.
[0036] In the present invention, the pH of the sulfanilamide-containing Borax buffer is preferably selected to be 7.0.
[0037] The technical solutions provided by the present invention are described in detail below with reference to examples, which should not be construed as limiting the protection scope of the present invention.
[0038] Example 1 0.1500 g of Ti3C2-MXene is added to the ALD chamber and deposition is performed at 120 °C with high purity N2 as the carrier gas at a flow rate of 50 sccm into the ALD chamber. Cu is obtained by reacting Cu(damp)2 with Et2Zn using a heating mantle while Et2Zn and Cu(damp)2 are maintained at 100 °C and 25 °C, respectively. The two precursors are alternately pulsed into the ALD chamber to adsorb onto the MXene powder, and N2 is used to thoroughly remove residual precursors and by-products. To ensure sufficient adsorption in one deposition cycle, 200 consecutive Cu(damp)2 pulses and 200 consecutive Et2Zn pulses are performed. One ALD deposition cycle consists of a 2 s Cu(damp)2 pulse, 5 s reaction, and 20 s Cu(damp)2 rinse, followed by a 0.5 s Et2Zn pulse, 5 s reaction, and 20 s Et2Zn rinse. After one deposition cycle, the SA-Cu-MXene catalyst with a single atom distribution pattern is obtained.
[0039] Example 2 0.1500 g of Ti3C2-MXene is added to the ALD chamber and deposition is performed at 120 °C with high purity N2 as the carrier gas at a flow rate of 50 sccm into the ALD chamber. Cu is obtained by reacting Cu(damp)2 with Et2Zn using a heating mantle while Et2Zn and Cu(damp)2 are maintained at 100 °C and 25 °C, respectively. The two precursors are alternately pulsed into the ALD chamber to adsorb onto the MXene powder, and N2 is used to thoroughly remove residual precursors and sub-products. To ensure sufficient adsorption in one deposition cycle, 150 consecutive Cu(damp)2 pulses and 180 consecutive Et2Zn pulses are performed. One ALD deposition cycle consists of a 2 s Cu(damp)2 pulse, 5 s reaction, and 20 s Cu(damp)2 rinse, followed by a 0.5 s Et2Zn pulse, 5 s reaction, and 20 s Et2Zn rinse. After three deposition cycles, a C-Cu-MXene catalyst with a cluster distribution pattern is obtained.
[0040] Example 3 0.1500 g of Ti3C2-MXene is added to the ALD chamber and deposition is performed at 120 °C with high purity N2 as the carrier gas at a flow rate of 50 sccm into the ALD chamber. Cu is obtained by reacting Cu(damp)2 with Et2Zn using a heating mantle while Et2Zn and Cu(damp)2 are maintained at 100 °C and 25 °C, respectively. The two precursors are alternately pulsed into the ALD chamber to adsorb onto the MXene powder, and N2 is used to thoroughly remove residual precursors and sub-products. To ensure sufficient adsorption in one deposition cycle, 100 consecutive Cu(damp)2 pulses and 50 consecutive Et2Zn pulses are performed. One ALD deposition cycle consists of a 2 s Cu(damp)2 pulse, 5 s reaction, and 20 s Cu(damp)2 rinse, followed by a 0.5 s Et2Zn pulse, 5 s reaction, and 20 s Et2Zn rinse. After 150 deposition cycles, the F-Cu-MXene catalyst with a distribution pattern of metal thin film is obtained.
[0041] Figure 1 shows the spherical aberration electron micrographs of the composite catalysts obtained in Example 1 and Example 2 of the present invention, which show the presence of bright points (white links) of single atoms (Figure 1a and b) and clusters (Figure 1c and d) on the surface of MXene. It is clear that copper is present in a distribution pattern of single atoms and clusters.
[0042] FIG. 2 shows the copper K-edge XANES spectrum of the composite catalyst obtained in Example 2 of the present invention, based on CuO, Cu2O and Cu foil. The absorption edge of the sample is closest to Cu2O and Cu foil. Therefore, the Cu valence of C-Cu-MXene is metallic Cu. 0 Higher than Cu 1+ appears to be lower.
[0043] As seen in Figure 3, the cluster-like distributed composite catalyst (C-Cu-MXene) exhibited a major peak at 2.2 Å, which corresponds to Cu-Cu coordination, indicating that copper clusters were successfully supported on the surface of C-Cu-MXene. According to the R-space fitting of EXAFS, the Cu-Cu coordination number was about 5.2.
[0044] Figure 4 shows the EXAFS fitting curve of the C-Cu-MXene sample. According to the EXAFS parameter R space fitting, the coordination number of the Cu second shell layer is about 5.2, the average bond length of Cu is 2.52 Å, and according to the above, Cu5 is the main species.
[0045] Example 1 The catalysts obtained in Examples 1-3 catalyzed the activation of peroxymonosulfate (PMS) to degrade antibiotic contaminants in water:
[0046] At a temperature of 25±1°C, 0.075g of catalyst powder is added into 150mL of sulfanilamide-containing Borax buffer (pH=7), so that the concentration of sulfanilamide is 15mg / L. In the whole reaction process, the pH of the solution remains stable. Then, 0.2mM of peroxymonosulfate (PMS) is added into the mixed solution. 0.9mL of the mixed solution is taken with a syringe and filtered through a 0.22μm membrane. The contaminant concentration in the sample is measured using high performance liquid chromatography (HPLC).
[0047] Figure 5 shows the decomposition rate profiles of sulfanilamide in PMS systems activated with composite catalysts with different copper distribution patterns. The decomposition rate of sulfanilamide in the PMS system activated with the composite catalyst with single atom distribution (SA-Cu-MXene) was about 65.4% in 60 min, which was 42.4% higher than that of the PMS system activated with pure MXene. In particular, the addition of C-Cu-MXene increased the decomposition rate of sulfanilamide by 73.9% within 60 min compared with the pure MXene-activated PMS system. Meanwhile, when the composite catalyst with a copper thin film distribution pattern (F-Cu / MXene) was added, the decomposition rate of sulfanilamide increased by only 16.2%. The above results indicate that the composite catalysts with different copper loading patterns can promote the activation of PMS and the decomposition of pollutants. It was also found that the composite catalysts obtained with different copper loading patterns have different effects on promoting the decomposition of pollutants.
[0048] The PMS utilization rate of the composite catalysts with different copper distribution patterns is shown in Fig. 6. As shown in Fig. 6, the PMS utilization rates of the composite catalysts with single atom distribution, cluster distribution, and copper thin film distribution are 58.0%, 76.8%, and 37.9%, respectively, indicating that the metal distribution pattern has an effect on the PMS utilization rate.
[0049] Figure 7 shows the cyclic decomposition rate of sulfanilamide over the PMS-activated cluster-supported MXene composite catalyst. After three cyclic decomposition experiments, the removal rate of sulfanilamide was over 95%, indicating high stability.
[0050] Figure 8 shows that the distribution pattern of copper on the MXene surface affects the type and steady-state concentration of active species. The composite catalysts with copper distributed as single atoms or clusters mainly 1 O2 and SO4 ·- whereas the composite catalysts distributed as clusters produced a higher steady-state concentration. 1 O2 and SO4 ·- The composite catalyst distributed as a copper film 1 It can only produce O2.
[0051] Figure 9 shows that the distribution pattern of copper influences the degradation pathway of pollutants. As shown in Figure 9, when sulfanilamide was degraded by C-Cu-MXene / PMS system, the salt bridge current tended to increase with degradation time, and the current stabilized at 1.0 mA at 20 min, indicating that the contribution of the electron transport pathway in sulfanilamide degradation gradually increased. However, the currents of SA-Cu-MXene and F-Cu-MXene systems activated by PMS for sulfanilamide degradation decreased significantly with increasing degradation time, and the current of SA-Cu-MXene / PMS decreased from 2.0 mA to 1.2 mA at 50 min, and the current of F-Cu-MXene system further decreased from 2.0 mA to 11.1 mA at 20 min. These results indicate that the electron transport pathway is involved in the decomposition of sulfanilamide in all three types of copper-modified MXene-activated PMS, but the contribution of the electron transport pathway to the decomposition of sulfanilamide in the C-Cu-MXene-activated PMS system is smaller than that in the SA-Cu-MXene and F-Cu-MXene-activated PMS systems.
[0052] The distribution pattern of copper on the MXene surface affects the degradation pathway of pollutants. As shown in Figure 10, during the oxidative degradation of sulfanilamide by activating PMS with three kinds of Cu-MXene composite catalysts, the main products P1, P2, P3, P5, P8, P9, P10, P11, P12, P13, P14, P15 and P16 were detected. It is noteworthy that intermediates such as P4, P6, P7 and P8 (indicated by five-pointed stars in Figure 9) were produced more in the C-Cu-MXene / PMS system.
[0053] As can be seen from the above examples, the present invention provides a method for modifying the decomposition pathway of peroxymonosulfate (PMS) pollutants using the distribution pattern of copper, and a method for preparing and applying a composite catalyst. The present invention simultaneously controls the decomposition pathway of sulfanilamide and the toxicity of intermediate products by adjusting the parameters of the preparation process, modifying the distribution pattern of copper, adjusting the active sites of the catalyst, and modifying the activation pathway of peroxymonosulfate (PMS) and the type of active species generated. Metal loading by atomic layer deposition technology can achieve uniform deposition, precise control of catalyst composition and dispersion, and the decomposition efficiency of antibiotic pollutants by the activation of peroxymonosulfate (PMS) of the obtained composite catalyst is significantly improved.
[0054] It should be noted that the above content is only a preferred implementation method of the present invention, and a person skilled in the art can make many improvements and optimizations without departing from the principle of the present invention, and these improvements and optimizations shall also be regarded as the protection scope of the present invention.
Claims
1. The copper distribution pattern is used to change the decomposition pathway of pollutants such as peroxymonosulfate (PMS), When the distribution pattern of copper is a single atom distribution, the active material produced is 1 O 2 and S.O. 4 ・- and When the distribution pattern of copper is cluster distribution, the active substances produced are 1 O 2 and S.O. 4 ・- and When the copper distribution pattern is copper film distribution, the active material produced is 1 O 2 is A method comprising:
2. According to the method according to claim 1, If the copper distribution pattern is a single atom distribution, 1 O 2 The steady-state concentration of is 0.39 × 10 -9 ~0.42 x 10 -9 M -1 ・s -1 , S.O. 4 ・- The steady-state concentration of is 0.02 x 10 -9 ~0.04 x 10 -9 M -1 ・s -1 and If the copper distribution pattern is clustered, 1 O 2 The steady-state concentration of is 1.5 × 10 -9 ~1.6 x 10 -9 M -1 ・s -1 , S.O. 4 ・- The steady-state concentration of is 0.21 x 10 -9 ~0.23 x 10 -9 M -1 ・s -1 and If the copper distribution pattern is copper film distribution, 1 O 2 The steady-state concentration of is 0.10 x 10 -9 ~0.12 x 10 -9 M -1 ・s -1 is A method comprising:
3. A method for preparing Cu-MXene composite catalysts with different copper distribution patterns, Ti as a film formation support 3 C 2 - Using MXene and nitrogen as a carrier gas, a bis(dimethylamino-2-propoxy)copper(II), min. 98% Cu(dmap)2 precursor and a diethyl zinc precursor are alternately irradiated to a deposition support by pulse irradiation, and a Cu-MXene composite catalyst having different copper distribution patterns is obtained in different deposition cycles. A method comprising:
4. The method according to claim 3, characterized in that the flow rate of nitrogen is between 40 and 60 sccm.
5. 5. A method according to claim 3 or 4, characterized in that the alternating pulses are carried out at 110-140°C.
6. The method according to claim 5, characterized in that the Bis(dimethylamino-2-propoxy)copper(II), min. 98% Cu(dmap)2 precursor is preheated at a temperature of 90-110°C and the diethylzinc precursor is preheated at a temperature of 20-30°C.
7. A method according to any one of claims 3, 4 or 6, characterized in that the precursor Bis(dimethylamino-2-propoxy)copper(II), min. 98% Cu(dmap)2 is pulsed 50-200 times and the precursor Diethylzinc is pulsed 50-200 times.
8. According to the method of claim 7, the number of cycles of deposition is 1 to 150, and one deposition cycle consists of a 2 second pulse of Bis(dimethylamino-2-propoxy)copper(II), 98% or more Cu(dmap)2 (Bis(dimethylamino-2-propoxy)copper(II), min. 98% Cu(dmap)2) precursor, a 5 second reaction, and a 20 second wash of Bis(dimethylamino-2-propoxy)copper(II), 98% or more Cu(dmap)2 (Bis(dimethylamino-2-propoxy)copper(II), min. 98% Cu(dmap)2) precursor; The method then consisted of a 0.5 second pulse of diethylzinc precursor, a 5 second reaction and a 20 second wash of diethylzinc precursor.
9. A Cu-MXene composite catalyst with different copper distribution patterns obtained by the method according to any one of claims 1 to 8, The Cu-MXene composite catalysts having different copper distribution patterns include a Cu-MXene composite catalyst having a single atom distribution pattern, a Cu-MXene composite catalyst having a cluster distribution pattern, and a Cu-MXene composite catalyst having a metal film distribution pattern.
23. A method comprising:
10. The Cu-MXene composite catalyst with different copper distribution patterns according to claim 9 is used to decompose antibiotic pollutants in water by activating peroxymonosulfate (PMS).
Citation Information
Patent Citations
CuO-Fe2O3 / Mxene composite material for water treatment and purification as well as preparation method and application of CuO-Fe2O3 / Mxene composite material
CN113181947A
Cu / MXene monatomic catalyst as well as preparation method and application thereof
CN115090286A
Preparation method of Cu-Mxene two-dimensional nanosheet material and application of Cu-Mxene two-dimensional nanosheet material to electrocatalyst
CN115181989A
Cu2+1O-coated MXene Fenton-like catalyst as well as preparation method and application thereof
CN115445645A
Copper metal film, method for preparing the same, and method for forming copper interconnect for semiconductor device using the same
US20160305024A1